Detection and Functional Verification of Noncanonical Splice Site Mutations in Hereditary Deafness - Chen, Penghui; Wang, Longhao; Chai, Yongchuan; Wu, Hao; Yang, Tao (Frontiers in Genetics, 2021)
Splice site mutations contribute to a significant portion of the genetic causes for mendelian disorders including deafness. By next-generation sequencing of 4 multiplex, autosomal dominant families and 2 simplex, autosomal recessive families with hereditary deafness, we identified a variety of candidate pathogenic variants in noncanonical splice sites of known deafness genes, which include c.1616+3A>T and c.580G>A in EYA4, c.322-57_322-8del in PAX3, c.991-15_991-13del in DFNA5, c.6087-3T>G in PTPRQ and c.164+5G>A in USH1G. All six variants were predicted to affect the RNA splicing by at least one of the computational tools Human Splicing Finder, NNSPLICE and NetGene2. Phenotypic segregation of the variants was confirmed in all families and is consistent with previously reported genotype-phenotype correlations of the corresponding genes. Minigene analysis showed that those splicing site variants likely have various negative impact including exon-skipping (c.1616+3A>T and c.580G>A in EYA4, c.991-15_991-13del in DFNA5), intron retention (c.322-57_322-8del in PAX3), exon skipping and intron retention (c.6087-3T>G in PTPRQ) and shortening of exon (c.164+5G>A in USH1G). Our study showed that the cryptic, noncanonical splice site mutations may play an important role in the molecular etiology of hereditary deafness, whose diagnosis can be facilitated by modified filtering criteria for the next-generation sequencing data, functional verification, as well as segregation, bioinformatics, and genotype-phenotype correlation analysis.